Pengaruh kesenian Wayang dalam proses berkembangnya Islam di Nusantara - Riansyah, Muhammad (Maliki Interdisciplinary Journal, 2024)
Puppet performances in the spread of Islam in the archipelago are discussed in this article. The author used historical methods to search for and collect various relevant sources to compile this article with the aim of explaining the history of wayang and its origins, how wayang can be used to spread Islam, and the role of figures in spreading Islam through wayang. Wayang has been part of Javanese cultural arts for 1,500 years. The use of wayang as a tool to spread Islam is a consequence of its early history as an artistic performance to spread Islam. Wali Songo's role in spreading Islam through wayang is very important.